Determining the Articles Acceptance Using Logic of Fuzzy Inference System Tsukamoto - Fauzi, Juwita Annisa; Rahman, Nukleon Jefri Nur; Handayani, Anik Nur; Mahamad, Abd Kadir (Letters in Information Technology Education (LITE), 2020)
Publication of scientific article is now getting bigger, but the process of the scientific article acceptance takes a long time. The longest stage in the process, especially, is in the review process. The process about article assessment consists of many criteria which cause a very high level of subjectivity. Computerized system on the assessment of the scientific article acceptance apply a reasoning scheme using Fuzzy Inference Tsukamoto Logic; therefore, by using the logic, the duration issue in the assessment process can be handled fast.